History of a model plant growth-promoting rhizobacterium, Bacillus velezensis GB03: from isolation to commercialization - Jang, Seonghan; Choi, Soo-Keun; Zhang, Huiming; Zhang, Shouan; Ryu, Choong-Min; Kloepper, Joseph W. (Frontiers in Plant Science, 2023)
Bacillus velezensis strain GB03 is a Gram-positive rhizosphere bacterium known for its ability to promote plant growth and immunity. This review provides a comprehensive overview of the research on GB03 from its initial discovery in Australian wheat fields in 1971 to its current applications. Recognized as a model plant growth-promoting rhizobacterium (PGPR), GB03 has exhibited outstanding performance in enhancing the growth and protection of many crop plants including cucumber, pepper, wheat, barley, soybean, and cotton. Notably, GB03 has been reported to elicit plant immune response, referred to as induced systemic resistance (ISR), against above-ground pathogens and insect pests. Moreover, a pivotal finding in GB03 was the first-ever identification of its bacterial volatile compounds, which are known to boost plant growth and activate ISR. Research conducted over the past five decades has clearly demonstrated the potential of GB03 as an ecofriendly substitute for conventional pesticides and fertilizers. Validating its safety, the U.S. Environmental Protection Agency endorsed GB03 for commercial use as Kodiak® in 1998. Subsequently, other compounds, such as BioYield TM , were released as a biological control agent against soil-borne pathogens and as a biofertilizer, utilizing a durable spore formulation. More recently, GB03 has been utilized as a keystone modulator for engineering the rhizosphere microbiome and for eliciting microbe-induced plant volatiles. These extensive studies on GB03 underscore its significant role in sustainable agriculture, positioning it as a safe and environmentallyfriendly solution for crop protection.